Isolamento, cultivo, caracterização e criopreservação de células tronco mesenquimais derivadas de membrana amniótica, geléia de Wharton e sangue do cordão umbilical de fetos bovinos - Campos, Loreta Lemes [UNESP] (2014)
Stem cells are undifferentiated cells with a high proliferation potential. These cells can be characterized by their in vivo ability to self-renew and to differentiate into specialized cell lines. The most used stem cell type, in both human and veterinary field, is the mesenchymal stem cells (MSC). Nowadays, there is a great tendency to use stem cells derived from fetal tissues, such as amniotic membrane (AM), extravascular matrix of umbilical cord (EMUC) and umbilical cord blood (UCB), which can be obtained non-invasively at delivery time. Thus, the aim of this study was to isolate, characterize and differentiate. MSC derived from bovine fetal annexes cow dairy neonates after assisted delivery and of fetus obtained in slaughterhouse. Cells were isolated by enzymatic digestion of the tissue fragments with 0,1% collagenase solution. Six samples of AM and EMUC at delivery time, six samples of AM and EMUC at first third of pregnancy and six samples of UCB at secondary third of pregnancy were subjected to morphology evaluation, immunocytochemistry, flow cytometry and in vitro osteogenic, adipogenic and chondrogenic differentiation. Moreover, sample were cryopresrved and evaluated for viability by flow citometri. All samples showed adherence to plastic and fibroblast-like morphology. Immunocytochemistry revealed expression of CD 44, NANOG and OCT-4 and lack of expression of MHC II in MSC from all samples. Flow cytometry demonstrated that cells from all samples expressed CD 44, lacked CD 34 expression and showed low expression of MHC II. They were also capable of trilineage mesenchymal differentiation and showed 80-90% viability after cryopreservation. According to the results, AM, EMUC and UCB, either obtained at delivery time or from slaughterhouse, are a painless and non-invasive source of MSC and can be used for stem cell bank creation